Nitric Oxide Is Associated With Heterosis of Salinity Tolerance in Brassica napus L. - Zhang, Yihua; Cheng, Pengfei; Wang, Jun; Abdalmegeed, Dyaaaldin; Li, Ying; Wu, Mangteng; Dai, Chen; Wan, Shubei; Guan, Rongzhan; Pu, Huiming; Shen, Wenbiao (Frontiers in Plant Science, 2021)
Heterosis is most frequently manifested as the superior performance of a hybrid than either parent, especially under stress conditions. Nitric oxide (NO) is a well-known gaseous signaling molecule that acts as a functional component during plant growth, development, and defense responses. In this study, the Brassica napus L. hybrid (F1, NJ4375 × MB1942) showed significant heterosis under salt stress, during both the germination and post-germination periods. These were in parallel with the changes in redox and ion homeostasis. The stimulation of endogenous NO was more pronounced in hybrid plants, compared to parental lines, which might be mediated by nitrate reductase. Proteomic and biochemical analysis further revealed that protein abundance related to several metabolic processes, including the chlorophyll biosynthesis, the proline metabolism, and the tricarboxylic acid cycle metabolism pathway, were greatly suppressed by salt stress in the two parental lines, respect to those in hybrid. Above responses in hybrid plants were intensified by a NO-releasing compound, but abolished by a NO scavenger, both of which were matched with the changes in chlorophyll and proline contents. Taken together, we proposed that heterosis derived from F1 hybridization in salt stress tolerance might be mediated by NO-dependent activation of defense responses and metabolic processes.